Intraindividual variability of the movement patterns in expert handball throwers - Rojas, J.; Gutierrez, M.; Ortega, M.; Parraga, J.; Campos, J. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this study was to compare players' intra-individual variability in the throwing movement pattern in support, throwing to the four corners of the goal, and in the presence of the goalkeeper in handball. Four players from the Spanish first division participated as subjects, plus seven goalkeepers. The start of the goalkeepers' movements was recorded from a force platform with a frequency of 500 Hz, while the throw was videotaped by two video cameras synchronized at the same frequency with the force platform. The variability in the movement pattern faked the goalkeepers. The kinetic chain is proximal-distal (P-D) a temporal sequence orientated to reduce the stress in the joint of the shoulder. The inertia of the trunk reduced the time of execution and determined the instant of throwing depending on the goalkeeper´s movements.